Hand hygiene compliance of healthcare professionals in an emergency department - Caroline Zottele; Tania Solange Bosi de Souza Magnago; Angela Isabel dos Santos Dullius; Adriane Cristina Bernat Kolankiewicz; Juliana Dal Ongaro (SciELO, 2017)
Abstract OBJECTIVE To analyze compliance with hand hygiene by healthcare professionals in an emergency department unit. METHOD This is a longitudinal quantitative study developed in 2015 with healthcare professionals from a university hospital in the state of Rio Grande do Sul. Each professional was monitored three times by direct non-participant observation at WHO's five recommended moments in hand hygiene, taking the concepts of opportunity, indication and action into account. Descriptive and analytical statistics were used. RESULTS Fifty-nine healthcare professionals participated in the study. The compliance rate was 54.2%. Nurses and physiotherapists showed a compliance rate of 66.6% and resident physicians, 41.3%. When compliance was compared among professional categories, nurses showed greater compliance than resident physicians (OR = 2.83, CI = 95%: 1.09-7.34). CONCLUSION Hand hygiene compliance was low. Multidisciplinary approaches could be important strategies for forming partnerships to develop learning and implementation of hand hygiene practices.